Quarta revolução industrial e o papel do Estado brasileiro na pesquisa e desenvolvimento - Costa, Hirdan Katarina de Medeiros (2020)
The Industrial Revolutions can be understood as historical moments of technological development, which carry humanity to productive, social and economic transformations. The 4th Revolution presents elements absent in previous ones, considering the conjugation of disruptive technologies with exponential characteristics. In this context, science, technology and innovation (ST&I) can be understood as basis for the accumulation of knowledge and techniques that culminate in these Revolutions, functioning as a circular feedback loop. In this scenario, the complexity of interaction between the several social players, including the state, in order to create a favorable environment and investments aimed to ST&I stand out. As such, this research’s main objective is to analyze the Brazilian state’s role and its limits of intervention in the context of ST&I, from the viewpoint of the Constitutional Economic Order from 1988. As specific objectives, this work will examine the arguments aimed at preclude the state from ceasing to promote or obstruct technology; likewise the instruments existent in the Science, Technology and Innovation Legal Framework will be verified. The methodology of the work is bibliographic review, utilizing the qualitative method to analyze the state’s instruments of action in ST&I. The results point to an analysis of the changes of the Legal Framework, with pretense to allow a favorable legal environment to the maturation of the National Innovation System, though the presence of several instruments that promote ST&I. With that, it was pointed out the incoherence of public policies that obstruct technologies with the objectives of the Legal Framework. The absorption of sustainability concepts in social and environmental matters to qualify ST&I policies is noticeable, however it was not found that such insertions would be barriers, but new dimensions of efficiency and accountability within the definition of ST&I. Therefore, in the final considerations, it was found that the role of the state is crucial for the strengthening of ST&I, including rules with investment obligations in specific segments were able to stimulate these sectors, bringing satisfactory results over the period analyzed